Phenomenology and Sense. Husserl and Heidegger on the Discussion on the Practical Character of Existence - Herrera, Hugo Eduardo (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This article analyses the attempts of Edmund Husserl and Martin Heidegger to endorse the original practical character of existence and the contributions of both philosophers in the criticism and detection of diverse effects for human life generated by the reduction of the practical sense of existence by positivist positions. In this context the author compares both attempts and explains certain advantages of the heideggerian arguments in order to give answers to problems that are not solved satisfactorily by Husserl.